2020
DOI: 10.1155/2020/8815461
|View full text |Cite
|
Sign up to set email alerts
|

Remote Identity Verification Using Gait Analysis and Face Recognition

Abstract: Biometric identification has verified its effectiveness in personal identity verification because of the uniqueness and noninvasion. In this research, we tend to apply the detection of biometric information to a remote sensing system for the purpose of security area monitoring. Our system is established by collecting signals from the coming individuals via the remote measurement in the specific condition where both kinds of data are detected to determine the identity. Specifically, the measuring of gait signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The study reported signi cant improvements in recognition accuracy compared to conventional methods, highlighting the synergies between gait patterns and anthropometric data. Researchers extended this line of research, exploring the complementary nature of anthropometric data and gait features [17]. These studies collectively underscore the potential of anthropometric data integration to advance the capabilities of gait recognition systems.…”
Section: Integration Of Anthropometric Datamentioning
confidence: 92%
“…The study reported signi cant improvements in recognition accuracy compared to conventional methods, highlighting the synergies between gait patterns and anthropometric data. Researchers extended this line of research, exploring the complementary nature of anthropometric data and gait features [17]. These studies collectively underscore the potential of anthropometric data integration to advance the capabilities of gait recognition systems.…”
Section: Integration Of Anthropometric Datamentioning
confidence: 92%
“…The study reported significant improvements in recognition accuracy compared to conventional methods, highlighting the synergies between gait patterns and anthropometric data. Researchers extended this line of research, exploring the complementary nature of anthropometric data and gait features [21]. These studies collectively underscore the potential of anthropometric data integration to advance the capabilities of gait recognition systems.…”
Section: Integration Of Anthropometric Datamentioning
confidence: 92%
“…Huan et al [21] makes use of acceleration sensors in smartphones and explores a way to analyze the gait of a person. Si et al [22]. have made use of remote sensing system for security area monitoring which collects signals from people walking towards the system where the data of their walking and face is extracted and is processed to recognize the person.…”
Section: Relevant Workmentioning
confidence: 99%